Personnel management of the military organizational structure and directions of improving its efficiency - Tikhonov, Hrygorii; Kirilkin, Yevhenii; BodnarОleh (Social Development and Security, 2021)
The article is devoted to the study of the relationship between the elements of the personnel management system and its impact on improving the capabilities of the military organizational structure. The modern scientific tendencies concerning definition of a management system and questions on increase of its efficiency are considered, the basic problem aspects of questions of personnel management are formed. Defined indicators that are proposed to evaluate the personnel management system, and the procedure for calculating efficiency ratios.